2017
DOI: 10.1016/j.jpubeco.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The response of deferred executive compensation to changes in tax rates

Abstract: Available online xxxx JEL Classification: G30 H24 H32 J33 Keywords: Deferred income Executive compensation Tax policy Elasticity of taxable incomeGiven the increasing use of stock options in executive compensation, we examine how taxes influence the choice of compensation and document that income deferral is an important margin of adjustment in response to tax rate changes. To account for this option in the empirical analysis, we explore deferral by estimating how executives' choice of compensation between cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Still, on the contrary, if the executive's compensation was inadequate, the tax aggressiveness was high. This tendency is also consistent with Hansen et al (2016) and Gorry et al (2015), suggesting the relationship between executive compensation and tax avoidance. Based on this description, the hypothesis is raised as follows: H3: Executive compensation affects tax avoidance Tax avoidance is an effort made by taxpayers to minimize tax payments.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Still, on the contrary, if the executive's compensation was inadequate, the tax aggressiveness was high. This tendency is also consistent with Hansen et al (2016) and Gorry et al (2015), suggesting the relationship between executive compensation and tax avoidance. Based on this description, the hypothesis is raised as follows: H3: Executive compensation affects tax avoidance Tax avoidance is an effort made by taxpayers to minimize tax payments.…”
Section: Introductionsupporting
confidence: 82%
“…The study of Huang et al (2018) revealed that if companies pay higher compensation money to executives, tax avoidance will be lower for companies registered in China. Gorry, Hassett, Hubbard, and Mathur (2015) report their empirical findings that there is a significant impact on taxes due to executive compensation. This statement is reinforced by the results of Hansen, Lopez, and Reitenga (2016), which prove that there is a tax relationship with sufficient compensation.…”
Section: Introductionmentioning
confidence: 99%